2021
DOI: 10.3389/fphys.2021.700723
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Strategies for Reconditioning Motor Output and Postural Balance in Frail Older Subjects Prone to Falls

Abstract: In frail older subjects, the motor output of the antigravity muscles is fundamental in resisting falls. These muscles undergo accelerated involutions when they are inactive and the risk of falling increases during leisure and domestic physical activity. In order to reduce their risk of falling, frail older subjects limit their physical activities/exercises. The problem is that the less they exercise, the less they are able to exercise and the greater the risk in exercising. Hence, a vicious circle sets up and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
4
1
1
Order By: Relevance
“…There is a significant body of evidence suggesting that decreased motor abilities are closely tied to the risk of falls. 13 , 14 Our analysis, which used binary logistic regression, revealed that motor dysfunction, sensory impairment, and speech disorders were significant influencing factors linked to falls (P < 0.01, as noted in Tables 1 and 2 ). Within our cohort of 60 patients who experienced falls, a striking 95% (or 57 patients) had motor dysfunctions.…”
Section: Discussionmentioning
confidence: 79%
“…There is a significant body of evidence suggesting that decreased motor abilities are closely tied to the risk of falls. 13 , 14 Our analysis, which used binary logistic regression, revealed that motor dysfunction, sensory impairment, and speech disorders were significant influencing factors linked to falls (P < 0.01, as noted in Tables 1 and 2 ). Within our cohort of 60 patients who experienced falls, a striking 95% (or 57 patients) had motor dysfunctions.…”
Section: Discussionmentioning
confidence: 79%
“…Estes músculos sofrem declínios acelerados quando estão inativos durante o lazer e a atividade física doméstica, ocasionando o risco de queda, tendo como resultado para a pessoa idosa a perda da independência, uma vez que em idosos frágeis, o menor distúrbio postural pode causar uma queda. (28) Quanto à disfunção familiar, o estudo conduzido pela Rede de Vigilância à Saúde da pessoa idosa (REVISI) em Goiânia (GO) analisou a prevalência e os fatores associados à disfuncionalidade familiar (APGAR Familiar), bem como a capacidade funcional da comunidade idosa. Foram investigadas 934 pessoas idosas, e os resultados indicaram percentual semelhante ao encontrado no presente estudo, 18,1% apresentaram disfunção familiar.…”
Section: Discussionunclassified
“…With regard to the motor component of the postural function, the motor output (muscle strength and power, rate of force development, force variability, and movement control), the joint contribution (mobility, amplitude, stabilization, stiffness), the synergistic muscle command (agonist/antagonist co-activation reduction), and the inter-segmental coordination (phase, anti-phase) are optimized with training and experience ( Field, 2011 ; Nagai et al, 2012 ; Freyler et al, 2014 ; Verhoeven and Newell, 2016 ; Paillard, 2021 ).…”
Section: Adaptations Of Various Components Of Postural Function To Tr...mentioning
confidence: 99%
“…Moreover, frail and/or older subjects clearly displaying a weakness of the lower-limb muscles need multimodal training with stimulation of neuromuscular function (aimed at improving muscle strength, muscle power/rate of force development, force variability/coordination) combined with stimulation of the postural function to improve postural balance in order to reduce the risk of falling (cf. Paillard, 2021 ). In any case, muscle strength and especially muscle power should be developed or maintained through the regular practice of physical/sport activities throughout adult life since the force-velocity (force rapidly) quality would be associated with postural performance in healthy older subjects ( Orr et al, 2006 ) and young subjects ( Johnson and Woollacott, 2011 ).…”
Section: Intervention Strategy To Optimize Postural Adaptationsmentioning
confidence: 99%